Plasticity in nest placement of the Turtle Dove (Streptopelia turtur): experimental evidence from Moroccan agro-ecosystems. (1st May 2014) - Hanane, Saâd
A total of 364 Turtle Dove (Streptopelia turtur) nests were found in the Tadla irrigated area during the 2006–2009 breeding seasons. Of these, 135 were located in orange orchards, 178 in olive orchards and 51 in olive hedgerows. Gaussian generalised linear modelling was used to model the nest height and the nest–trunk distance according to the characteristics of olive and orange trees in the orchards and hedgerows. Tree height and type of plantings had the strongest effects on both nest height (R2 = 0.67) and nest–trunk distance (R2 = 0.48). Overall, the same pattern of Turtle Dove nest height was recorded in the three types of plantings, whereas different patterns were noted for the nest–trunk distance. The results provide evidence of non-random patterns of nest placement in olive and orange agro-ecosystems. This game species exhibits adaptive behavioural plasticity in nest placement and appears to be well-adapted to the olive and orange grove conditions in this region. This high adaptability is beneficial to maintaining the species in these artificial habitats. Additional quantitative studies are needed to improve our understanding on the mechanisms driving the choice of nest placement by Turtle Doves in this agricultural man-made environment.